Analysis of RPL37A, MTSS1, and HTRA1 expression as potential markers for pathologic complete response and survival - Carrara, Guilherme Freire Angotti (2021)
Background: Non-metastatic locally advanced breast carcinoma (LABC) treatment involves neoadjuvant chemotherapy (NCT). We evaluated the association of clinical–pathological data and immunoexpression of hormone receptors, HER2 and Ki67, and new biomarkers, RPL37A, MTSS1 and HTRA1, with pathological complete response (PCR) or tumour resistance (stable disease or disease progression), disease-free survival (DFS) and cancer-specific survival (CSS). Methods: This is a retrospective study of 333 patients with LABC who underwent NCT. Expression of MTSS1, RPL37A and HTRA1/PRSS11 was evaluated by immunohistochemistry in TMA slides. Cutoff values were established for low and high tumour expression. ROC plotter evaluated response to NCT. Chi-square test for factors related to PCR, and Kaplan–Meier test and Cox model for factors related to DFS and CSS were prformed. Results: The mean follow-up was 70.0 months and PCR rate was 15.6%. At 120 months, DFS rate was 32.5% and CSS rate was 67.1%. In multivariate analysis, there was an association between: (1) necrosis presence, intense inflammatory infiltrate, ER absence, HER2 molecular subtype and high RPL3A expression with increased odds of PCR; (2) lymph node involvement (LNI), high Ki67, low RPL37A and high HTRA1 expression with increased risk for NCT non-response; (3) LNI, high proliferation, necrosis absence, low RPL37A and high HTRA1 expression with increased recurrence risk; (4) advanced LNI, ER negative tumours, high HTRA1, low RPL37A expression and desmoplasia presence with higher risk of cancer death. Conclusion: RPL37A is a potential biomarker for response to NCT and for prognosis. Additional studies evaluating HTRA1 and MTSS1 prognostic value are needed.